The rise of new university presses and academic-led presses in the UK - Stone, Graham (Septentrio Conference Series, 2017)
Watch the VIDEO here. The recent report, Changing publishing ecologies: A landscape study of new university presses and academic-led publishing, shows a discernible increase in new UK publishing initiatives entering the sector over the last few years. The new university press strand of the research consisted of a survey, which collected 43 responses, the academic-led press strand was informed by interviews with 14 scholar-led presses. Taking different approaches for these two types of press, the report captures the take-up, reasoning and characteristics of these initiatives, as well as their future plans. It complements previous research, such as OAPEN-UK, the UK National Monographs strategy, the Jisc/OAPEN Investigating OA monograph services project and the new Knowledge Exchange Landscape Study on Open Access Monographs which will be published in September 2017. These new publishing initiatives have a potentially disruptive effect on the scholarly communication environment, providing new avenues for the dissemination of research outputs and acting as pathfinders for the evolution of academic publishing and the scholarly record. The findings of the research carried out as part of this report provide an evidence base for future support for both new university presses and academic-led publishing initiatives to help create and maintain a diverse publishing ecology. The report concludes with a series of recommendations to help support and foster new developments in this space, share best practice, collaboration and the tools and services to facilitate further innovation. For example, the report recommends to support community building for both NUPs and ALPs, the establishment of guidelines for setting up a press, the provision of legal advice and guidelines for preservation and dissemination, and the development of future projects to support these new initiatives. In particular, the community professed a need for the development of a toolkit that would aid both existing NUPs and academic-led presses, as well as those universities and academics that are thinking about setting up their own publishing initiatives. This paper will precis the report, before exploring the progress made in establishing an infrastructure for UK university and academic-led presses. Finally, the author would like to encourage other European countries to build upon this research by adapting the questions asked in the research. This would allow for a more complete view of European NUPs and ALPs and the demand for shared approach, such as a wider set of best practice guidelines, workshops and a European Library Publishing Coalition for library presses.